The cost of soil erosion in sub-Saharan Africa: Why the time to act is now - Bolo, Peter; Kihara, Job; Kinyua, Michael; Waswa, Boaz S. (2025)
Soil erosion is a silent crisis eroding Africa’s future. In sub-Saharan Africa (SSA), nearly half a billion hectares of land (494 million ha - an area larger than the entire European Union) is being degraded. The main culprit is soil erosion, stripping away vital nutrients from farmlands, threatening food production, and robbing the continent of billions of dollars every year. This document, based on the latest evidence reported in a recent policy brief, lays out the true cost of soil erosion, and what can be done to reverse it: a call for a “zero erosion campaign.”